Analisis Kelayakan Finansial CV Astika Rizki Nursery di Kota Batu - Angraeni, Siska Pramudya; Relawati, Rahayu; Baroh, Istis (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Batu City is recognized as a potentially fertile agricultural area, and the high market demand makes citrus nursery businesses promising. Oranges have a consistent market demand both as a direct consumption fruit and as a raw material for the food and beverage industry. Additionally, technological advancements and changes in consumer consumption patterns also impact the agricultural market, including citrus nurseries. Technical challenges such as seed quality, plant disease management, and other production factors need attention. The sustainability of the citrus nursery business also depends on the availability of local resources, including workforce, water, and agricultural infrastructure support. Financial feasibility analysis becomes a strategic step to evaluate the sustainability and development potential of CV Astika Rizki Nursery's citrus nursery business in Batu City. By understanding market conditions, operational challenges, and resource availability, this analysis is expected to provide a comprehensive and in-depth view to support effective and sustainable business management. Financial feasibility analysis was conducted using the NPV, Net B/C Ratio, IRR, and Payback Period methods. The results indicate that the investment in citrus nursery is feasible to continue, with an NPV value of IDR 867,015,035.71, an IRR of 44%, and a Payback Period of 1 year 2 months. Additionally, other methods such as Gross B/C Ratio and Net B/C Ratio also demonstrate the feasibility of the investment. Thus, this document provides a comprehensive and in-depth perspective to support effective and sustainable business management in the citrus nursery business in Batu City.